2014
DOI: 10.5539/jas.v6n11p103
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Activity and Growth Performance of Shrimp Post Larvae Litopenaeus vannamei Under Light and Dark Condition

Abstract: The present study was conducted to elucidate the effects of light and dark condition on the feeding activity of shrimp, Litopenaeus vannamei. Examination on the ingestion rate of shrimps at different sizes (0.5, 1.0 and 1.5 cm total length, TL) under light and dark condition was conducted using newly hatched frozen Artemia nauplii. For each condition, shrimp were let to ingest known number of Artemia nauplii for 30 minutes, thereafter the remaining Artemia nauplii was counted. For the observation of eye struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
2
6
0
3
Order By: Relevance
“…Similar photoperiod associated gonad maturation was observed in Cambarus virilis [35], Procambarus simulans [36] and in Procambarus clarkii [37,38]. In Litopenaeus vannamei feeding activity, growth and survival of smaller animals were affected by photoperoid [39]. Further, studies of Tidwell et al [40] indicated that continual light conditions have positive impact on survival of Macrobrachium rosenbergii juveniles during the nursery phase.…”
Section: Influence Of Environmental Variables On Reproductionsupporting
confidence: 53%
“…Similar photoperiod associated gonad maturation was observed in Cambarus virilis [35], Procambarus simulans [36] and in Procambarus clarkii [37,38]. In Litopenaeus vannamei feeding activity, growth and survival of smaller animals were affected by photoperoid [39]. Further, studies of Tidwell et al [40] indicated that continual light conditions have positive impact on survival of Macrobrachium rosenbergii juveniles during the nursery phase.…”
Section: Influence Of Environmental Variables On Reproductionsupporting
confidence: 53%
“…These findings may reflect the ontogenetic development of chemoreceptors to find food sources compared to larval stages that rely more on vision (Sanudin et al . ). However, more research into ontological changes in chemoreception vs vision is necessary and presents an exciting area for future studies.…”
Section: Influences On Shrimp Feeding Behaviourmentioning
confidence: 97%
“…Sanudin et al . () examined L. vannamei larvae (0.5 cm total length (TL)) and demonstrated a greater ingestion rate of feed in light conditions compared to dark. As the shrimp grew (up to 1–1.5 cm TL), differences between light and dark conditions did not influence the feeding activity to the same degree.…”
Section: Influences On Shrimp Feeding Behaviourmentioning
confidence: 99%
“…Para juvenis de Farfantepenaeus paulensis Wasielesky et al (2012) observaram que a maior luminosidade também favoreceu o desenvolvimento da espécie em relação ao ambiente sombreado. Em sistemas de cultivo com bioflocos a sobrevida de L.vannamei também esteve associada ao incremento do número de horas de fotoperíodo (Baloi et al, 2013;Viet et al, 2017;Reis et al, 2019) e mesmo ao porte dos indivíduos (Sanudin et al, 2014). Neste caso, pode ser que a influencia da luminosidade nos camarões seja variável com as condições de contorno (i.e.…”
Section: Fonte Deunclassified